THE EXPERIMENTAL DETERMINATION OF TOXICOLOGICAL PROPERTIES, ULCERATIVE AND LOCAL IRRITATING EFFECT OF THE THICK BEAN EXTRACT - Рибак, В.А.; Малоштан, Л.М.; Павиченко, О.В. (World of Medicine and Biology, 2015)
A great importance has the chemical and pharmacological study of plants and biologically active substances, derived from them, to generate some hypoglycemic agents of the plant origin. Besides a high pharmacological activity, one of the most important requirements for medications is their safety. It is proved that the patients who use actively some herbal medicines to treat diabetes, need smaller doses of insulin and peroral hypoglycemic drugs.The purpose of the research has been to study acute toxicity of the thick bean extract (TBE) for intragastric administration to mice at doses of: 500 mg/kg, 5000 mg/kg, 10000 mg/kg and 15000 mg/kg and intraperitoneal administration to rats at doses of: 10 mg/kg, 100 mg/kg, 1000 mg/kg and 3000 mg/kg, which corresponds to the different classes of the substances toxicity, as well as potential irritant and ulcerogenic actions of the TBE.The study of the TBE acute toxicity has been conducted by the method of Shtabskii B.M.. Investigations of a possible damaging effect of the TBE (at doses – 10 mg/kg, 40 mg/kg and 100 mg/kg) on the gastric mucosa and 12 duodenal ulcer have been performed on Wistar rats by the method of J. Marazzi-Uberti. An investigation of the effect of TBE and acetylsalicylic acid (at doses of 40 mg/kg and 100 mg/kg) on the stomach and intestines of the animals has been performed on Wistar rats for 14 days under conditions when ethanol induced gastric ulcers. Ulcers of the gastric mucosa have been caused by the intragastric administration of 5 ml/kg of absolute alcohol to the animals fasted for 24 hours. The study of local irritating action of the TBE has been conducted on Chinchilla rabbits. A solution of aqueous suspensions of the TBE, stabilized by Tween-80, has been injected to the conjunctival eye bags of the animals by 1-2 drops for 5 days.While studying the acute toxicity of the TBE by intragastrically administration to the mice (at doses of 500 mg/kg, 5000 mg/kg, 10000 mg/kg and 15000 mg/kg) and intraperitoneal administeration to the rats (at doses of 10 mg/kg, 100 mg/kg, 1000 mg/kg, 3000 mg/kg and 5000 mg/kg) we have established that the death of the experimental animals have not occured. The TBE refers to the V toxicity class of the substances i.e. practically non-toxic ones, according to the toxicity classification of substances by Sidorov K.K. The TBE shows no ulcerogenic effect at doses of 20 mg/kg and 40 mg/kg. A minor ulcerogenic action of the TBE has been revealed only at a dose of 100 mg/kg on the gastric mucosa of the rats. The TBE has not potentiated ulcerogenic activity of ethanol on the model of ethanol gastric ulcers. The TBE has not shown a local irritating action on the mucous conjunctiva eyes of the rabbits.The TBE is a promising medicine for the further pharmacological studies to investigate the effect on the state of coagulation homeostasis in experimental insulin-dependent type 2 diabetes in order to prevent the risk of angiopathy.
Keywords: acute toxicity; ulcerogenic and local irritating effect; metformin; thick bean extract